A REVIEW ON THE MEMORY POTENTIAL EFFECT OF “POLYGALA TENUIFOLIA, LYCII FRUCTUS AND CENTELLA ASIATICA” - MINAKSHI; AJEET PAL SINGH; AMAR PAL SINGH; Singh, MEENAKSHI MALHOTRA (Innovare Journal of Ayurvedic Sciences, 2024)
Traditional medicines have been used as memory enhancers worldwide since ancient times. There are a number of herbs used for this purpose due to their memory potential property. Sage, Ginkgo Biloba, brahmi, ginseng, cinnamon, ginger, rosemary, Salvia Herbs, and Chinese celery are some examples of memory enhancer plants. In this article, we have reviewed the role of three medicinal plants (Polygala tenuifolia, Lycii fructus, and Centella asiatica) in the treatment of memory disorders. These plants have magical effects to increase memory function. There are several studies that show their memory potential effect.